Inaccessibility to double‐stranded RNAs in plastids restricts RNA interference in Bemisia tabaci (whitefly). Issue 9 (13th May 2020) - Dong, Yi; Yang, Yong; Wang, Zican; Wu, Mengting; Fu, Jinqiu; Guo, Jianyang; Chang, Ling; Zhang, Jiang
Abstract: Background: RNA interference (RNAi) has emerged as a promising technology for insect pest control. Because of the accumulation of high levels of long double‐stranded RNAs (dsRNAs) in plastids, it was previously shown that expression of dsRNAs from plastid genome led to higher mortality of some insect pests with chewing mouthparts than dsRNAs expression from nuclear genome. However, whether plastid‐expressed dsRNAs have effects on phloem sap‐sucking pests is unknown. In this study, we compared the RNAi effects of nuclear transgenic and transplastomic plants on the whitefly Bemisia tabaci, a serious sap‐sucking pest. Results: Nuclear transgenic and transplastomic tobacco plants were developed for the expression of dsRNA against BtACTB gene of Bemisia tabaci, respectively. Feeding nuclear transgenic plants to Bemisia tabaci resulted in reduced gene expression of BtACTB and survival rate, and impaired fecundity of Bemisia tabaci . We did not observe any effects of transplastomic plants on Bemisia tabaci fitness. Furthermore, we found that the inability of B. tabaci to obtain dsRNAs from plastids might restrict its RNAi responses. Conclusion: Our study indicated that the expression of dsRNAs in nuclear transgenic plants was more effective than that in transplastomic plants for the control of Bemisia tabaci . The inaccessibility of Bemisia tabaci to plastids contributes to the inefficiency of plastid‐mediated RNAi. Our findings are of great significance to future optimization of transgenically delivered RNAi approaches for efficient controlling of sap‐sucking pests. © 2020 Society of Chemical Industry Abstract : Two approaches for plant transgenically delivery of RNA interference (RNAi) for control sap sucking insect whitefly were side‐by‐side compared, which revealed that whitefly can suck up RNAi molecules from cytoplasm of phloem cells while not from plastids, contributing to the inefficiency of plastid‐mediated RNAi for controlling whitefly.